2021
DOI: 10.1073/pnas.2020054118
|View full text |Cite
|
Sign up to set email alerts
|

Immature HIV-1 assembles from Gag dimers leaving partial hexamers at lattice edges as potential substrates for proteolytic maturation

Abstract: The CA (capsid) domain of immature HIV-1 Gag and the adjacent spacer peptide 1 (SP1) play a key role in viral assembly by forming a lattice of CA hexamers, which adapts to viral envelope curvature by incorporating small lattice defects and a large gap at the site of budding. This lattice is stabilized by intrahexameric and interhexameric CA-CA interactions, which are important in regulating viral assembly and maturation. We applied subtomogram averaging and classification to determine the oligomerization state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 53 publications
(78 reference statements)
2
47
0
2
Order By: Relevance
“…2d), indicating the complete hexagons are not assembly units of HIV. In concert with this observation, a recent study shows the Gag dimers are the basic assembly units of the HIV-1 particle 28 . These protrusions could be Gag dimers and are prone to structural changes during proteolytic cleavage .…”
Section: Application To Virus Tomogramsmentioning
confidence: 70%
“…2d), indicating the complete hexagons are not assembly units of HIV. In concert with this observation, a recent study shows the Gag dimers are the basic assembly units of the HIV-1 particle 28 . These protrusions could be Gag dimers and are prone to structural changes during proteolytic cleavage .…”
Section: Application To Virus Tomogramsmentioning
confidence: 70%
“…The escape mutants reduce six-fold symmetry throughout the 6HB, which is partially recovered by BVM in particular cases. Our free energy calculations demonstrate that loss of six-fold symmetry facilitates helical uncoiling, which precedes proteolytic cleavage (19,22). Consequently, the efficacy of BVM is due to additional resistance to symmetry loss.…”
Section: Discussionmentioning
confidence: 81%
“…More recently, cryo-EM and MD analysis suggested that the edges of the fissures within immature HIV-1 capsid particles expose incomplete Gag hexamers, which could be the potential substrates for protease cleavage (22). This would imply that only the protomers within incomplete 6HBs may be in a dynamic helix-coil equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, sequence alignments revealed little conservation of putative L-Domains across viruses, suggesting that the model for ALIX recruitment may only occur in select herpesvirus nuclear egress pathways. Perhaps in cases of ESCRT-III dependent nuclear egress, an edge of the NEC containing the L-Domain sequence is exposed to the nucleoplasm to be recognized for ALIX-mediated membrane budding and scission, much like how HIV-1 Gag recruits ALIX to the plasma membrane [71]. Although this model places the L-Domain of the NEC proximal to the nuclear envelope, this proposed mechanism is not unlike the recruitment of ESCRTs seen for beta-retroviruses and spuma-retroviruses where ESCRT binding is predicted to occur close to the plasma membrane [72,73].…”
Section: The Necs Of Herpesviruses Form Gag-like Assemblies That Interact With Alix and Are Required For Efficient Nuclear Egressmentioning
confidence: 99%